Genotoxicity effects of Newcastle disease virus strain AF2240 in vitro and in vivo - Mohamed Shahrin, Zaid (2012)
Newcastle disease virus (NDV) is a member of the Paramyxoviridae that causes severe economic losses in the poultry industry worldwide. Several strains of NDV were reported to induce cytolysis to cancerous cell lines. Newcastle disease virus is a potential oncolytic as it can replicate up to 10,000 times better in cancerous cells than in most normal human cells. In this study, a local strain of NDV AF2240 was evaluated for its genotoxicity properties against breast cancer cell line (4T1 cancer cell lines) and normal cell lines (3T3 fibroblast cell lines). The cytolysis effects of NDV AF2240 were determined using Microtetrazolium (MTT) assay. Further studies were carried out to observe the genotoxicity potential of NDV AF2240 using comet assay. In the assay, individual cell was screened for DNA damage after treatment with NDV AF2240. The clastogenetic effect of NDV AF2240 was also observed using bone marrow micronucleus assay. The safety of the virus was investigated in vivo using 9 New Zealand white albino rabbit. The irritation effects of the virus were observed on rabbit eyes. The inhibition concentration (IC50) for NDV AF2240 to inhibit 50 % of 4T1 cancer cells population were 32 HA unit/ml and 64 HA unit/ml for co-culture and monolayer methods, respectively. No significant cytolytic effect was observed on normal 3T3 fibroblast cell lines at the same virus titer used in breast cancer cell lines. The proliferation rates of treated breast cancer cell was reduced significantly with time and titration of virus compared to the untreated control. It was noticed that 4T1 breast cancer cell line treated with NDV AF2240 gave a strong genotoxic response as the formation of comet tail were significantly longer than 3T3 fibroblast cell line treated with NDV AF2240. The study indicated that NDV AF2240 did not damage the DNA of normal cells but caused damage to breast cancer cells exclusively. It was noticed that the proliferation rate of normal erythrocytes to polychromatic erythrocytes of mice after treatment with NDV AF2240 were normal as compared to positive control. There was no significant increase in the induction of micronucleus formation in young erythrocytes which indicates that the virus has no clastogenic effect, thus will not result in chromosomal damage in mitotic apparatus of reproductive system in mice model. It was noticed that NDV AF2240 did not cause any irreversible effects to rabbit eyes. It only caused mild conjunctival redness as observed in group treated with 2048 HA unit of NDV and disappeared 72 hours post treatment. Scanning electron microscopy (SEM) evaluation of rabbit epithelial cornea surface revealed that the distribution of light, medium and dark reflex cells, the size, morphology of cell boundaries, structure and the distribution of microvilli of cornea treated with NDV AF2240 at 64 HAU, 512HAU and 2048 HAU, were similar to the control cornea. It was observed that NDV AF2240 did not cause any ocular disease to the corneal surface. Therefore, it is possible to use NDV strain AF2240 in clinical trials since it is proven to be an effective anti-cancer agent against breast tumor, and NDV AF2240 exhibited none or minimal side effects to animal model used in this study. However, further study need to be carried out to learn more about the effects of NDV AF2240 on human in terms of understanding the viral replication and localization in preclinical studies before it can be used extensively in clinical trial phase.